8 Muestra internacional de performance (utopia/distopia). - Alvarado, Karina; Santamarina, Guillermo; Instituto Nacional de Bellas Artes, Mexico (Mexico : Ex Teresa Arte Actual, 1999)
Bergmann, Janno ; Bruguera, Tania ; Chalem, Henri-Louis ; Martel, Richard ; Couillard, Paul ; Davis, Kelly ; Gaudin, Lydia ; Gomez, Luis Carlos ; Hershiser, Kate ; Young, Kum ; López, Francisco ; Martel, Richard ; Merino, Santiago ; Minujin, Marta ; Mora, Ulises ; Muñoz, Victor ; Peña, Maria Esther ; Peñaloza, Maricruz ; Qi, Sheng ; The Rachel Rosenthal Company ; Recke, Nikolaj ; Renvall, Markus & Seppo ; SEMEFO ; Smigileska, Ewas ; Kazmierczak, Wladyslaw ; Villa, Mario ; Zuluaga, Alonso ; Barney, Matthew ; Schneemann, Carolee ; Finn-Kelcey, Rose ; Minujin, Marta ; Stelarc
Spaans
8 Muestra internacional de performance (utopia/distopia), Ex Teresa Arte Actual, Mexico, Del 13 al 23 de octobre 1999
boek